Emulsion electrosynthesis in the presence of power ultrasound Biphasic Kolbe coupling processes at platinum and boron-doped diamond electrodes - Wadhawan, J; Del Campo, F; Compton, R; Foord, J; Marken, F; Bull, S; Davies, S; Walton, D; Ryley, S (2001)
The electrochemical oxidation of aliphatic carboxylic acids, hexanoic, heptanoic, and lauric acid, under biphasic conditions is studied as a model system for ultrasound enhanced Kolbe electrosynthesis processes. Power ultrasound is used to generate an in situ emulsified medium and to remove reaction products continuously from the electrode surface. A clean and highly efficient process at platinum electrodes with formation of 'one electron' products only occurs in marked contrast to processes in monophasic media. For hexanoic acid the Kolbe dimer product R-R is formed in up to 75% yield with 45% current efficiency at 0.18 A cm-2 current density and in the presence of 190 W cm-2 ultrasound. The mechanism is explained in terms of a dynamically modified electrode surface, at which hydrophobic products are immediately 'trapped' via partitioning into a non-polar organic phase and transported away into the emulsion system. Kolbe electrosynthesis is undertaken both at platinum electrodes and at free-standing polycrystalline boron-doped diamond electrodes, in order to minimize the surface erosion effect induced by power ultrasound. The type and yield of products obtained from the biphasic Kolbe electrolysis process at diamond electrodes are essentially identical to those observed at platinum and based on this observation, the presence of a biphasic reaction layer at the electrode surface is postulated to govern the process. © 2001 Elsevier Science B.V.